The effects of cyberbullying victimization on depression and suicidal ideation among adolescents and young adults: a three year cohort study from India - Chanda Maurya; T. Muhammad; Preeti Dhillon; Priya Maurya (BMC Psychiatry, 2022)
Abstract Background Cyberbullying victimisation is considered a global public health issue concerning the psychological development of adolescents that oftentimes persists into adulthood. The current study explored the longitudinal relationship between cyberbullying victimisation and depression and suicidal ideation among adolescents and young adults, given the scarcity of such studies in poor-resource settings like India. Methods Data were drawn from the “Understanding the Lives of Adolescents and Young Adults” (UDAYA- 2015-16 and 2018–19) surveys conducted in two most-populated Indian states of Uttar Pradesh and Bihar. Bivariate and logistic regression analysis was conducted to fulfil the objectives of the study using a sample of 4428 and 11,864 adolescent (aged 10–19 years) male and female cohorts, respectively. Results The prevalence of cyberbullying victimization increased from 3.8% to 6.4% among female respondents and 1.9% to 5.6% among male respondents over three years. About 33% of females and 16.6% of males had depressive symptoms in their young adulthood. Nearly 7.5% females compared to 2.3% of males, reported that they have seriously considered attempting suicide in the past one year. Adolscents who experienced cyberbullying victimization were 2.07 times more likely to have depressive symptoms comapared to those who did not experience cyberbullying victimization. Similarly, adolescents who experienced cyberbullying victimization were 2.50 times more likely to have suicidal ideation than their counterparts with no experience of cyberbullying victimization. Conclusion The findings suggest that cyberbullying victims are at higher risk of depressive symptoms and suicidal thoughts and these adverse effects persist for longer period. Therefore, cyberbullying and related mental health problems need to be addressed with more efficient strategies such as increased awareness of nuances of online harassments among adolescent and young adult population.